LAND PRODUCTIVITY IMPROVEMENT THROUGH GIVING FERTILIZER N, P, K AND PLANTING TIME OF PEANUT (ARACHIS HYPOGAEA L.) IN THE INTERCROPPING SYSTEM WITH MAIZE (ZEA MAYS L. ) - Febri Dian Handayani; Laode Sabaruddin; La Ode Afa (Agrotech Journal, 2016)
The purpose of this research is to investigate the productivity of land by N,P,K fertilizer and time of planting peanuts in intercropping systems with maize. This research was conducted applying experimental garden at Agriculture Faculty of Halu Oleo University, Kendari. The research was conducted in the dry season, from August to November 2015. The research was arranged meant by split plot design with two replications. The main plot is NPK fertilizer dose (S) consisted of three levels namely 56-36-25 kg ha-1 (S1), 90-54-25 kg ha-1 (S2) , 124-72-50 kg ha-1 (S3). The subplots was planting time of peanuts with maize intercropping (W) consisted of three levels, namely planting time of peanuts 10 days before planting (DBP) maize (W1), planting peanuts with maize simultaneously (W0), and planting peanuts 10 days after planting (DAP) maize (W2). There are nine treatment combinations of two factors mentioned. Each combination treatment was repeated three times, coupled with each of the three experimental plots for monoculture cropping systems of peanuts and maize. The total number of units was 45 units experimental. Data experiments were analyzed by using analysis of variance followed by Duncan's Multiple Range Test. The results showed that the treatment time 10 DBP planting peanuts with maize to increase productivity, reduce competition index and efficient of the use fertilizer. Provision of fertilizer NPK 124-72-50 kg ha-1 dose can increase growth and yield of maize and peanuts